The Future of Six Party Talks: Options and Prospects - Kwang-Ho CHUN (International Journal of Supply Chain Management, 2018)
Recent positive political developments in the Korean peninsula are getting more attention from many political, economic, and military options. The Six Party talk is obviously the one. The Six Party talks to achieve optimal supply chain that has taken place over the past decade have been the only real progress, making a diplomatic tool that has sought to stem nuclear proliferation within the Korean peninsula. However, considerable doubt exists as to how effective they have been and whether they remain a relevant means by which the issue can be solved. This paper looks at events that have transpired over the course of the talks for supply chain and contextualizes how beneficial they have been. It is critical of the parties involved for their individualistic attitudes towards the talks and places particular emphasis on China and the U.S in its assessment of the extent to which the parties are working towards the stated goals. Since the talks for achieving optimal supply chain stalled in 2009, relationships in and around the Korean Peninsula have become increasingly strained with Kim Jong Un assuming the role as North Korean leader, a series of attacks as well as weapons testing, it is now highly relevant that an assessment of diplomatic methods be made. The paper concludes that while the talks for supply chain offer potentially the fairest and swiftest resolution of the issues, the parties involved are exploring independent means of coercion before they will resume. Finally, with North Korean ties as strained as ever, it is set out that a return to diplomacy will unlikely herald a rapid Change in the security and political environment.